Clinical Evaluation Followed by Molecular Diagnosis in a Multiplex Pedigree of Angelman Syndrome: A Case Report - Azam Ahmadi Shadmehri; Fahimeh Akbarian; Jamileh Rezazadeh Varaghchi; M. Amin Tabatabaiefar (Journal of Sciences, Islamic Republic of Iran)
Angelman syndrome (AS) is a neurodevelopmental disorder characterized by severe developmental delay or intellectual disability caused by either disruption of the maternal UBE3A gene or deletion in the maternal 15q11-q13. Diagnosis of AS in two siblings with normal four-generation history was confirmed through a staged genetic evaluation, G-banding karyotype, Fluorescence in situ Hybridization analysis, and methylation pattern in 15q11-q13. Despite detecting impaired methylation patterns in the region of interest, distinguishing the imprinting defects from uniparental disomy (UPD) was not feasible since we did not have access to the parents' sample. However, regarding the low risk of AS recurrence within families with UPD in the literature and the healthy family history, mosaicism of cryptic imprinting center deletion in the mother's germline should be the most probable cause of AS recurrence in our cases.